Pattern of BAER abnormalities in neonatal hyperbilirubinemia - Singh AK, Dutt HK and Singh G (Journal of Applied Pharmaceutical Science)
This study was done to determine the various abnormalities of Brain Auditory Evoked Response (BAER) in neonates with hyperbilirubinemia and to correlate the specific BAER abnormality with a particular range of bilirubin levels. Prospective study was done in 100 cases in a tertiary care hospital over a period from 2007-2008. All cases with hyperbilirubinemia were subjected to BAER test. Fifty five percent (n=44) out of 80 cases showed abnormal BAER test and 24 of them showed bilaterally in babies having peak serum bilirubin levels of more than 20mg/dL. Seventy five percent (n=33) showed prolong interpeak latency in wave III-V indicating that the conduction from superior olivary complex (wave III) to inferior collicullus (wave V) were more commonly affected with peak levels of bilirubin when compared to control which were found to be statistically significant (p
Keywords: Auditory test, Encephalopathy, Serum bilirubin